The Effect of the SWBST Strategy on Reading Comprehension and Writing Skills of Cambodian Fourth-Grade Students - Rorthmony Norm; Da BOU; Smiror Vann; Linna Nin; Borey Chhen (Journal of Classroom Action Research, 2026)
Reading comprehension is crucial to students' academic achievement; however, some Cambodian primary school students struggle to comprehend written materials. This study investigates the impact of the Somebody-Wanted-But-So-Then (SWBST) instructional technique on reading comprehension and writing skills in Grade 4 students in Cambodia. The study employed a sequential explanatory mixed-methods design, commencing with a quantitative phase and subsequently transitioning to a qualitative phase. A quasi-experimental methodology assessed the effect of the SWBST strategy, while student interviews offered insights into their perspectives on the method. Findings indicate that students who received SWBST instruction outperformed their counterparts in the control group, especially in recognizing main ideas and summarizing texts. A substantial association exists between reading comprehension and writing proficiency, illustrating the intimate connection between two literacy skills. Students demonstrated favorable opinions towards the SWBST method, indicating enhanced engagement and comprehension during reading exercises. The results suggest that broader implementation of the SWBST technique in Cambodian primary schools may enhance literacy outcomes and cultivate a more conducive learning atmosphere. Keywords: primary education, reading comprehension, student perception, SWBST strategy, writing skill